716 Parenting techniques & factors associated with child maltreatment among children 11 to 17 years in Karachi, Pakistan. (1st September 2016) - Lakhdir, Maryam; Kadir, Masood; Azam, Iqbal; Parpio, Yasmin; Khan, Uzma; Razzak, junaid
Abstract : Background: Harsh disciplinary practices are considered common in developing countries. However, scientific evidence lacks to support this. Primary aim of this study was to determine the prevalence of different forms (physical, emotional maltreatment and neglect) of child abuse in Karachi, Pakistan. Methods: A cross sectional survey of 800 dyads (children ranging from 11–17 years old and their parent) were selected from 32 clusters of Karachi, using multistage cluster sampling between December 2014 to March 2015. A structured questionnaire adopted from International society of child abuse and neglect (International child abuse screening tool for parent and child). Prevalence of child maltreatment was estimated by mean child abuse score. MLR was used to assess the association of factors with outcome. Results: Mean score were 51.7 + 11.9 (child), 77.9 + 20.2 (mother) and 63.6 + 17.3 (father). Both parent and child responses revealed similar prevalence (43%) of child maltreatment. There is an interaction between parental exposures to childhood abuse and physical fighting with hard object among family members. Among children whom family always fight with each other and parents have exposure to childhood maltreatment, the mean estimated ICAST-Child score increases by 13.746 (95% CI: 7.193, 20.298). There is an interaction between age of mother and parental education. The estimated mean of ICAST-Child score increases 2.169 times for every 10 years increase in age of mother among children whom both formal have no formal school education as compared to children whom both parents have formal education. Conclusions: This study reflects hidden extent of child maltreatment and poly-victimisation in Karachi. Our findings provide evidence to raise public awareness about malpractices and highlight the need to develop positive parenting program.